Characterization and prediction of reservoir architecture and petrophysical properties in fluvial channel sandstones, middle Magdalena basin, Colombia - Ramón, J. C.; Cross, T. (CT&F - Ciencia, Tecnología y Futuro, 1997)
About 1 .600 m of core from two major oil fields, and 600 m of outcrop sections near to one of the fields, integrated with thousands of core, side-wall core and outcrop porosity and permeability measurements show that petrophysical properties and reservoir continuity change consistently with the Accommodation to Sediment Supply (A/S) ratio. Channel sandstones exhibit regular, recurring motifs that are associated with changes in A/S conditions. Manifesting the lowest accommodation conditions are amalgamated channel sandstones, up to 5-m-thick, with intraclast-rich bases capped by up to 1 -m-thick floodplain mudstones. AT higher A/S conditions, slightly amalgamated channel sandstones have lateral accretion surfaces and are capped by a thicker unit of floodplain mudstones. Channel sandstones in the highest A/S conditions are single-storied, possess conspicuous lateral accretion surfaces with thick mud drapes, and have a thick cover of overbank and floodplain deposits. Detailed well log correlations, oil production and pressure data support that the former are more lateral continuous while the I after form laterally discontinuous bodies embedded in floodplain mudstones. Petrophysical properties are closely associated with subtle variations in fades, particularly degree of preservation of original bedforms, and both are stratigraphically sensitive. Petrophysical properties of identical sedimentological fades change regularly as a function of itsstratigraphic position because of variations in the rates of accumulation and degree of preservation of the sediments. In the case of fluvial strata deposited during an increase in A/S, porosity and permeability are highest in trough cross-stratified sandstones immediately above channel scour bases, and decrease upward to the next scour base. Successive channel sandstones within the same stratigraphic sequence and channel sandstones from one sequence to the next have progressively lower porosity and permeability values in an overall increase in the A/S. An inverse trend is observed during a decrease in A/S.